A simulation model proposal to improve the productivity of container terminal operations through investment alternatives. Issue 2 (17th February 2019) - Sislioglu, Mucahit; Celik, Metin; Ozkaynak, Suleyman
ABSTRACT: Development of a container terminal (CT) closely deals with the efficiency of operating systems. This paper proposed a model to decide optimum investment alternatives to improve CT productivity. The proposed approach incorporates the parameters such as number of quay cranes, total length of a quay, yard trucks and yard cranes. The objectives of the model are minimizing the average ship turnaround time while maximizing the container throughput generated by the terminal. The methodology behind the model includes Discrete Event Simulation Model, data envelopment analysis (DEA) and cost-efficiency analysis. Considering container ship visits to Container Terminal Alpha (CT-A), the proposed model is demonstrated with 16 different investment scenario along with 10-months recorded operational data. The results addressed the Scenario LENG-2 (extent current total length of quays from 1.560 meters to 2.000 meters) as the optimal feasible solution for an investment in existing conditions. The model is also considered to besides contributions to investment decisions in CT, the developed framework might be extended to other transportation infrastructures.